2016
DOI: 10.1177/0954409716642486
|View full text |Cite
|
Sign up to set email alerts
|

Research on wheel hollow wear and dynamic performance of freight radial bogies

Abstract: The wheel wear properties of heavy haul bogies running on the Da-Qin railway line were measured. The hollow and asymmetric wear are indicated. The wheel/rail contact geometry relationship was calculated on the basis of the measured wheel profiles. The dynamic simulation model using SIMPACK software for C80BF Gondola with ZK7 radial bogie and C80B gondola with ZK6 cross brace bogie was established. The hollow depth effect on wheelset attack angle and lateral force was quantified. According to the actual conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Hollow tread is one of the important factors that determines wheel-rail contact location, contact size, and dynamic interaction of the railcar and track. 16 For these reasons, many studies have focused on hollow tread. Tavakkoli et al 17 investigated the effect of hollow-worn wheels on the dynamic behavior of a passenger coach and showed that hollow-worn wheels with a depth of greater than 2 mm induce lateral oscillations of the railcar and increased the risk of truck hunting.…”
Section: Approachmentioning
confidence: 99%
“…Hollow tread is one of the important factors that determines wheel-rail contact location, contact size, and dynamic interaction of the railcar and track. 16 For these reasons, many studies have focused on hollow tread. Tavakkoli et al 17 investigated the effect of hollow-worn wheels on the dynamic behavior of a passenger coach and showed that hollow-worn wheels with a depth of greater than 2 mm induce lateral oscillations of the railcar and increased the risk of truck hunting.…”
Section: Approachmentioning
confidence: 99%
“…Sui et al (2021) explored and analyzed the wheel diameter difference of heavy-haul freight vehicles and studied its effect on wheel wear. Li et al (2017) analyzed the causes of the wear and the influencing factors of wheel wear of heavy-haul freight vehicles by establishing two steering bogie models. Orlova and Boronenko (2010) analyzed the effect of the three major components of the steering bogie on the wheel flange by a dynamic model.…”
Section: Introductionmentioning
confidence: 99%
“…Te results show that concave tread does not directly lead to vehicle swaying instability, but will aggravate vehicle lateral vibration. Li et al [19] used multibody dynamics simulation software Simpack to compare the changes in vehicle operation safety index before and after wheel wear. Sawley et al [20,21] analyzed the changes of wheel-rail contact geometry, wheelset yaw angle, and lateral force with wheel concave wear by using experimental and simulation analysis techniques.…”
Section: Introductionmentioning
confidence: 99%